Pendampingan Peningkatan Kompetensi Menggunakan Quizizz Sebagai Asesmen Digital Bagi Guru SMA N 2 Bayang - Lisa Candra Sari; Martin Kustanti; Rezki Amelia; Novrianti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract. This assistance aims to increase competence in using Quizzizz as a digital assessment for teachers. The method used in this mentoring is the service learning method which follows three stages, namely